SEASONAL AND INTER-ANNUAL VARIABILITY OF THE ICE COVER IN THE GREENLAND SEA - L. A. Timokhov; N. A. Vyazigina; E. U. Mironov; A. V. Popov (Лëд и снег)
The results of studies of seasonal and inter-annual variability of the Greenland Sea ice cover are presented for the period from 1950 to 2016. Statistical characteristics of seasonal and inter-annual changes in the ice-covered area were calculated. Three clusters of typical seasonal variability were identified from the whole totality of all seasonal cycles. The first cluster presented a group of seasonal cycles in the period of maximum, the second one – the middle, and the third group – minimum areas of the winter ice cover. The estimates of correlation between changes in the ice areas in winter (February–March) or in summer (August–September) and areas of the following two months of a current year as well as in succeeding years were obtained. Empirical regularity of a variability of the ice cover during the annual cycle was established. This regularity is characterized by an existence of a ‘memory’ in the state of the ice cover, when a prehistory of the ice conditions determines to a certain extent the following phase. Analysis of inter-annual variability of the Greenland Sea ice cover did show a linear negative tendency in both winter and summer ice conditions. One-two year fluctuations were the most pronounced in the spectral density of inter-annual variations in the summer ice conditions. However, fluctuations with a longer period do also exist. With respect to contribution of hydrometeorological factors, the summer ice area is determined: (a) by conditions in the preceding winter, (b) by the atmospheric circulation, and (c) by the influence of warm Atlantic waters (about 20% of the total dispersion). Changes in the winter ice area depend: (a) mainly on the pre-winter state of ices (October–November), (b) on the influence of the Atlantic waters (about 30% of the total dispersion), and (c) on the heat balance and the atmospheric circulation (20% of the total dispersion). The results of this study may be used as a basis for the development of statistical models for analysis and prediction of long-term and climatic changes in the state of the ice cover in the Greenland Sea.